Preventive PCI versus culprit lesion stenting during primary PCI in acute STEMI: a systematic review and meta-analysis. Issue 1 (17th February 2014) - Pandit, Anil; Aryal, Madan Raj; Aryal Pandit, Aashrayata; Hakim, Fayaz Ahmad; Giri, Smith; Mainali, Naba Raj; Sharma, Prashant; Lee, Howard R; Fortuin, F David; Mookadam, Farouk
Abstract : Aim: The benefit of preventive percutaneous coronary intervention (PCI) in ST elevation myocardial infarction (STEMI) has been shown in randomised trials. However, all the randomised trials are underpowered to detect benefit in cardiac death. We aim to systematically review evidence on the cardiac mortality benefit of preventive PCI in patients presenting with acute STEMI in randomised patient populations. Methods: PubMed, Scopus, Cochrane and clinicaltrials.gov databases were searched for studies published until 30 September 2013. The studies were limited to randomised clinical trials. Independent observers abstracted the data on outcomes, characteristics and qualities of studies included. Fixed effect model was employed for meta-analysis. Heterogeneity of studies included was analysed using I 2 statistics. Results: In three randomised clinical trials published, involving 748 patients with acute STEMI and multivessel disease, 416 patients were randomised to preventive PCI and 332 to culprit-only PCI. Patients undergoing preventive PCI had significant lower risk of cardiovascular deaths (pooled OR 0.39, 95% CI 0.18 to 0.83, p=0.01, I 2 =0%), repeat revascularisation (pooled OR 0.28, 95% CI 0.18 to 0.44, p=0.00001, I 2 =0%) and non-fatal myocardial infarction (pooled OR 0.38, 95% CI 0.20 to 0.75, p=0.005, I 2 =0%) compared with culprit-only revascularisation. Conclusions: In patients presenting with acute STEMI and significant multivessel coronary artery disease, based on our data, preventive PCI is associated with lower risk of cardiovascular mortality compared with primary PCI of only the culprit artery. This finding needs to be confirmed in larger adequately powered randomised clinical trials.